ANSWER
![x=\frac{2-\sqrt{10}} {3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2-%5Csqrt%7B10%7D%7D%20%7B3%7D)
or
![x=\frac{\sqrt{10}+2} {3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B%5Csqrt%7B10%7D%2B2%7D%20%7B3%7D)
We have
![3x^2-4x-2=0](https://tex.z-dn.net/?f=3x%5E2-4x-2%3D0)
Since we cannot factor easily, we complete the square.
Adding 2 to both sides give,
![3x^2-4x=2](https://tex.z-dn.net/?f=3x%5E2-4x%3D2)
Dividing through by 3 gives
![x^2-\frac{4}{3}x= \frac{2}{3}](https://tex.z-dn.net/?f=x%5E2-%5Cfrac%7B4%7D%7B3%7Dx%3D%20%5Cfrac%7B2%7D%7B3%7D)
Adding
![(-\frac{2}{3})^2](https://tex.z-dn.net/?f=%28-%5Cfrac%7B2%7D%7B3%7D%29%5E2)
to both sides gives
![x^2-\frac{4}{3}x+(-\frac{2}{3})^2= \frac{2}{3}+(-\frac{2}{3})^2](https://tex.z-dn.net/?f=x%5E2-%5Cfrac%7B4%7D%7B3%7Dx%2B%28-%5Cfrac%7B2%7D%7B3%7D%29%5E2%3D%20%5Cfrac%7B2%7D%7B3%7D%2B%28-%5Cfrac%7B2%7D%7B3%7D%29%5E2)
The expression on the Left Hand side is a perfect square.
![(x-\frac{2}{3})^2= \frac{2}{3}+\frac{4}{9}](https://tex.z-dn.net/?f=%28x-%5Cfrac%7B2%7D%7B3%7D%29%5E2%3D%20%5Cfrac%7B2%7D%7B3%7D%2B%5Cfrac%7B4%7D%7B9%7D)
![\Rightarrow (x-\frac{2}{3})^2= \frac{10}{9}](https://tex.z-dn.net/?f=%5CRightarrow%20%28x-%5Cfrac%7B2%7D%7B3%7D%29%5E2%3D%20%5Cfrac%7B10%7D%7B9%7D)
![\Rightarrow (x-\frac{2}{3})=\pm \sqrt{\frac{10}{9}}](https://tex.z-dn.net/?f=%5CRightarrow%20%28x-%5Cfrac%7B2%7D%7B3%7D%29%3D%5Cpm%20%5Csqrt%7B%5Cfrac%7B10%7D%7B9%7D%7D)
![\Rightarrow (x)=\frac{2}{3} \pm {\frac{\sqrt{10}}{3}](https://tex.z-dn.net/?f=%5CRightarrow%20%28x%29%3D%5Cfrac%7B2%7D%7B3%7D%20%5Cpm%20%7B%5Cfrac%7B%5Csqrt%7B10%7D%7D%7B3%7D)
Splitting the plus or minus sign gives
![x=\frac{2- \sqrt{10}} {3}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B2-%20%5Csqrt%7B10%7D%7D%20%7B3%7D)
or
Answer:
Average speed = 100 km/h
Step-by-step explanation:
Given:
Total distance covered = 250 km
Total time taken = 8:30 am - 6:00 am = 2:30 hours = 2.5
Find:
Average speed.
Computation:
⇒ Average speed = Total distance covered / Total time taken
⇒ Average speed = 250 / 2.5
⇒ Average speed = 100 km/h
Answer:
6a - 28
Step-by-step explanation:
combine like terms
3a - 28 - 7a + 10a
3a - 7a + 10a = 6a
have a lovely day :)